Acetylcholine Muscarinic Receptors in Ventral Hippocampus Modulate Stress-Induced Anxiety-Like Behaviors in Mice - Mei, Li; Zhou, Yu; Sun, Yi; Liu, Hong; Zhang, Dengwen; Liu, Pingping; Shu, Haihua (Frontiers in Molecular Neuroscience, 2020)
Chronic stress exposure increases the risk of developing various neuropsychiatric illnesses. Ventral hippocampus (vHPC) is central to affective and cognitive processing and displays a high density of acetylcholine muscarinic receptors (mAChRs). However, the precise role of vHPC mAChRs in anxiety remains to be fully investigated. In this study, we found that chronic restraint stress (CRS) induced social avoidance and anxiety-like behaviors in mice, and increased mAChRs expression in the vHPC. Transient restraint stress increased the vHPC acetylcholine release in behaving mice. Moreover, CRS altered the synaptic activities and enhanced neuronal activity of the vHPC neurons. Using pharmacological and viral approaches, we showed that infusion the antagonism of mAChRs or decreasing their expression in the vHPC attenuated the anxiety-like behavior and rescued the social avoidance behaviors in mice, probably due to suppression of vHPC neuronal activity and their excitatory synaptic transmission. Our results suggest that changes of neuronal activity and synaptic transmission in the vHPC mediated by mAChRs may play an important role in stress induced anxiety-like behavior, providing a new insight into the pathological mechanism and potential pharmacological target for anxiety disorders.